An investigation into the effects of the abolishment of corporal punishment on learner behaviour in schools: A case of Epworth-Mabvuku-Tafara District, Harare Metropoilitan Province. - Chimbamu, Victor (Midlands State University, 2017)
The project was carried out recently for the purposes of investigating into the effects of the abolishment of corporal punishment on learner behaviour in schools in Epworth, Mabvuku-Tafara District in Harare Metropolitan Province. The researcher confined the study to six schools due to limited time and financial constraints as well as to make it workable. In the process of carrying out this research, the researcher succeeded in getting the effects into the abolishment of corporal punishment. The researcher used qualitative and quantitative research designs. These were used for clarity purposes so that the figures can be explained by descriptive writing to explain fully. The target population was made up of schools in Epworth –Mabvuku and Tafara. The sample was composed of heads, teachers and pupils from the 6 secondary schools. These were six out of twelve high schools in the district. 6 heads of schools, 36 teachers and 60 pupils, 10 from each school. For teachers 18 were females while 18 were males. The student sample comprised of 33 girls and 27 boys because the representation of students is now skewed in favour of girls (ZIMSTAT,2016). The school heads were 4 males and 2 females. The researcher used the stratified random sampling as a method of selection when sampling the population. In order to get a fairly balanced assessment, the researcher used different research instruments namely; questionnaires, interview, observations and document analysis. The researcher also consulted previous findings and secondary document before moving his own judgements. Although teachers and administrators are making some frantic efforts to provide other disciplinary methods. There are many factors which militate against the adoption of corporal punishment as it is also against the legal framework of the country. There are some other disciplinary methods which can be used in place of corporal punishment thus, the researcher which can be used in place of CP thus, and the researcher also found from the research is practiced in spite of its ban. The researcher used different research instruments for triangulation. The instruments are namely: questionnaires, interviews, observations and document analysis. The researcher also consulted previous research findings and secondary documents. The research found out that learner behaviour is affected by the ban, in most cases negatively, because of the confusion on what should be done concerning the disciplining of children. However, most students are in favour of the ban, which nonetheless contradicts cultural precepts, as it awards them freedom and also gives them the right to enjoy their liberties in a globalised world. On the other hand, the study discovered that teachers and administrators find it essential to employ what most described as “moderate” corporal punishment. The research recommended that policy should be reviewed to allow for a clearly understandable, publicised framework for the application of ‘moderate’ corporal punishment in schools in Zimbabwe. This, among other recommendations, involves the honest involvement of community in the policy making process at all levels. Teacher training on alternative methods of discipline and on the best application of corporal punishment was also advocated.